80 ANTIPLATELET ACTIVITY TO HIGH LOADING DOSE OF CLOPIDOGREL IS SIMILAR IN DIABETIC VERSUS NON-DIABETIC PATIENTS QUANTIFIED USING A NOVEL POINT-OF-CARE PLATELET AGGREGATION. (1st March 2005) - Nathan, S.; Kumar, A.; Dallow, Al R.; Amin, A.; Kelly, R. F.; Klein, L. W.; Calvin, J. E.; Bakris, G. L.
Abstract : Background: Recent data suggest significant interindividual variability in inhibition of platelet aggregation (IPA) and in non-response to clopidogrel. While diabetic thrombocytopathy is well recognized, it remains unclear if increased platelet aggregability seen in diabetes mellitus (DM) impacts the magnitude of IPA achieved with clopidogrel. Our study assesses whether DM impacts the degree of IPA induced by high-dose clopidogrel loading in patients with stable coronary artery disease. The secondary analysis investigated the correlation between achieved IPA and both glycemic control (HbA1C) and systemic inflammation (hs-CRP). Methods: IPA was quantified in 16 patients (7 DM, 9 non-DM) undergoing elective cardiac catheterization using a novel point-of-care assay (RUOP2Y12, Accumetrics) which measures IPA as a function of light transmittance to 4 μmol iso-TRAP and 20 μmol ADP stimulation, buffered to isolate ADP P2Y12 activity. IPA data analyzed included platelet reactivity units (PRU) and Δ % P2Y12 inhibition. All pts received ASA 325 mg daily for ≥ 7 days. A 600 mg oral loading dose of clopidogrel was administered, with IPA quantified at baseline and 4-6 hours after the clopidogrel dose. Results: DM and non-DM pts were similar with respect to baseline variables except hs-CRP [2.14 vs 0.35 mg/dL, p = 0.013], fasting glucose [219.3 vs 91.7 mg/dL, p = 0.0008] and HbA1C [10.7% vs 6.2%, p = 0.02]. Baseline PRU [286 vs 285] and % P2Y12 inhibition [19.2% vs 23.3%] were similar in both groups (p = NS). Overall 18.8% of pts evidenced<10% decrease in IPA and were deemed clopidogrel non-responders (2 DM, 1 non-DM, p = 0.55. Decrease in PRU (Δ PRU) was comparable between DM and non-DM pts [-125.7 ± 63.5 vs -113.8 ± 69.0, p = 0.88] as was Δ PRU % [-44.0 ± 30.2% vs -38.3 ± 21.6%, p = 1.0]. IPA was not correlated to hs-CRP, HbA1C or fasting glucose, respectively. Conclusions: The degree of IPA observed with this novel point-of-care assay within 4-6 hours of a 600 mg oral dose of clopidogrel was similar in DM and non-DM pts and comparable to published estimates obtained using light transmittance aggregometry. Among DM pts, glycemic state, glycemic control and in all pts, systemic inflammation do not appear to impact magnitude of IPA. Clopidogrel non-response was seen in approximately 20% of pts studied, without any clear predictive clinical or metabolic correlates. Additional validation of these findings is warranted in larger patient populations.